SEG Technical Program Expanded Abstracts 2008 2008
DOI: 10.1190/1.3054826
|View full text |Cite
|
Sign up to set email alerts
|

Addressing challenges in deep water Gulf of Mexico depth imaging through geologic models and acquisition simulation — The Tempest Project

Abstract: This paper describes the framework for constructing a realistic deep water Gulf of Mexico geologic model, marine acquisition simulation using full offset wave equation, application of various depth migration tests using the known model, and comparison of the model data results to real data results. The main focus of our project was to construct a realistic geological model, to simulate seismic acquisition using typical marine acquisition geometry and parameters and to image the data using prestack depth migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent developments in the area of GPUs have demonstrated that new architectures available in low‐cost graphical cards, called Compute Unified Device Architecture (CUDA), can be efficiently used for numerical simulations. The CUDA technology has been used to develop extremely efficient and accurate modeling tools in medicine, finance, seismology, and computer‐aided design, as shown in .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Recent developments in the area of GPUs have demonstrated that new architectures available in low‐cost graphical cards, called Compute Unified Device Architecture (CUDA), can be efficiently used for numerical simulations. The CUDA technology has been used to develop extremely efficient and accurate modeling tools in medicine, finance, seismology, and computer‐aided design, as shown in .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Besides complexity of simulating wave propagation in that media, different studies proved that strong velocity contrast of some geological units (like salt and anhydrate) with surrounding media is another great challenge for most of the seismic imaging algorithms and interoperation techniques (Albertin et al 2001;Ray et al 2004;Seitchick et al 2009). Examples of such settings are Gulf of Mexico, Avon canyon in Benin (Dahomey) basin (Olabode and Adekoya 2008), Jeffara basin in southeastern Tunisia (Gabtni et al 2012) and Qiangtang terrane, Tibetan plateau (Lu et al 2009).…”
Section: Introductionmentioning
confidence: 99%